The night ferry - Hammer, Lotte; Hammer, Søren (Hammer, Lotte. Konrad Simonsen series., 2018)
Sixteen children and four adults are killed in a devastating boat crash in Copenhagen. Detective Chief Superintendent Konrad Simonsen is called in, only to discover that this was no accident and that one of the passengers has a very personal connection to the homicide team. Reeling from this revelation and not knowing who to trust, Simonsen follows a trail that eventually leads him to Bosnia and a legacy of criminal misconduct. All evidence points towards one shady figure: a high-ranking army specialist with a suspicious past. But the more Simonsen digs, the further the truth slips from his grasp.